Analisis kedisiplinan belajar siswa kelas V Sekolah Dasar pada pembelajaran daring di era pandemi covid-19 - Suci Intan Sari; Sri Marmoah; Hadiyah Hadiyah (Universitas Sebelas Maret, 2022)
This research aims to determine the discipline of learning fifth grade student at SDN Dukuhan Kerten No. 58 Surakarta. This research used a qualitative approach with the subject being the fifth grade students of SDN Dukuhan Kerten No. 58 Surakarta. In data collection, researchers used methods of observation, interviews, documentation, and questionnaires. The techniques used in this study are data collection, data presentation, and drawing conclusions. To the test validity of the data using triangulation method. Based on the results of the research, it was concluded that the fifth grade students’ learning discipline SDN Dukuhan Kerten No. 58 Surakarta is good. This can be seen from the discipline students, among there; (1) students take online learning on time, (2) collect assignments according to the specified time, and (3) wearing uniforms when online learning takes place. The results showed discipline of learning had been implemented but was not maximal because of the obtacles : 1) limited smartphone, 2) availability of smartphone, 3) parental assistance, 4) parent’s attention to students, and 5) unstable internet network.